Athenian Trireme - Martins, Adolfo Miguel (iMARECULTURE H2020 Project: Advanced VR, iMmersive serious games and Augmented REality as tools to raise awareness and access to European underwater CULTURal heritagE, 2017)
These are detailed 3D models of an Athenian Trireme based on the research for the construction of real size model Olympias. There are several versions available in different formats.
Keywords: 3D model; Athenian Trireme; iMARECULTURE; 3D library